Latihan Keterampilan Psikologis Dalam Belajar Keterampilan Gerak (Penelitian Eksperimen Tentang Pengaruh Penetapan Tujuan dan Latihan Imajeri Mental Terhadap Hasil Belajar Keterampilan Gerak Bermain Bulutangkis Pada Anak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The purpose of this research is to examine the influence of goal setting and mental imagery training as two basic components of the psychological skill training on learning achievement of badminton motor skill. The subjects were 50 girls from Bandung FPOK Badminton School was devided to 4 experiment groups and one control group by random assignment. They were beginning girl athelets at 10-12 years old. It was hypothesized that dynamic goal would improve the development of high service and defensive skill more than process goal. It was also expected that mental imagery training would enhance high service and defensive clear skill more than without mental imagery training. The result of data computation using two ways factorial ANCOVA showed that goal setting and mental imagery training Oven a significant main effect, but no interaction both of them. Furthermore, the result of means adjusted pair camparations analysis indicated that effectivity of mental imagery training influenced by goal setting but not vice versa. Additional analysis revealed that mental imagery process of the mental imagery training group significantly higher than without mental imagery training, and generally all experimental group have learning achievement significantly higher than control group. Hence, based on the result of this study suggested that goal setting and mental imagery psychologial skill training can effectively incorporated in regular training program.